Decentralized capacity management and internal pricing - Dutta, Sunil; Reichelstein, Stefan (Review of Accounting Studies, 2010)
This paper studies the acquisition and subsequent utilization of production capacity in a multidivisional firm. In a setting where an upstream division provides capacity services for itself and a downstream division, our analysis explores whether the divisions should be structured as investment or profit centers. The choice of responsibility centers is naturally linked to the internal pricing rules for capacity services. As a benchmark, we establish the efficiency of an arrangement in which the upstream division is organized as an investment center, and capacity services to the downstream division are priced at full historical cost. Such responsibility center arrangements may, however, be vulnerable to dynamic hold-up problems whenever the divisional capacity assignments are fungible in the short-run, and therefore, it is essential to let divisional managers negotiate over their actual capacity assignments. The dynamic hold-up problem can be alleviated with more symmetric choice of responsibility centers. The firm can centralize ownership of capacity assets with the provision that both divisions rent capacity on a periodic basis from a central unit. An alternative and more decentralized solution is obtained by a system of bilateral capacity ownership in which both divisions become investment centers.